A prospective multicentre study of intravitreal injections and ocular surface in 219 patients: IVIS study. Issue 8 (18th March 2021) - Verrecchia, Sarah; Chiambaretta, Fredéric; Kodjikian, Laurent; Nakouri, Yasemin; El Chehab, Hussam; Mathis, Thibaud; Badri, Yannis; Chudzinski, Roman; Levron, Antoine; Chaperon, Mayeul; Agard, Emilie; Pradat, Pierre; et al.
Abstract: Purpose: To assess the impact of intravitreal injections (IVTI) on ocular surface of patients treated with multiple injections. Methods: Prospective, tricentric study conducted in patients treated with unilateral IVTI. An asepsis protocol with povidone‐iodine was used for all patients during IVTI. The primary endpoint was the difference between the pre‐IVTI Ocular Surface Disease Index (OSDI 1) score and that measured on day one (D1) post‐IVTI (OSDI 2). Secondary endpoints were the evaluation of predictive factors for OSDI scores, pain assessment on D1, and the Lacrydiag® analysis of tears from the injected eye versus contralateral eye before IVTI. Results: Two hundred and nineteen patients with a mean age of 75.9 ± 10 years were included. The mean OSDI2‐OSDI1 difference was 19.2 ± 20.6 (p < 0.001). The mean noninvasive tear break‐up time was 6.41 ± 4.59 seconds in the injected eye versus 7.36 ± 4.36 seconds in the contralateral eye (p < 0.001). In the multivariate analysis, the factors significantly associated with the OSDI 2 score were the OSDI 1 score (p < 0.001), the pain score on D1 (p < 0.001) the number of instilled glaucoma eye drop (p = 0.01) and a centre effect (centres 2 and 3 versus centre 1, p < 0.001). Conclusion: Our results confirm the impairment of the ocular surface and quality of life immediately after an IVTI. These results suggest 3 levels of action to improve the immediate tolerance: improving the basal status of the ocular surface, reducing the contact time with povidone‐iodine that might be toxic to the surface, and improving immediate post‐IVTI treatment.